Scopula anfractata sp. n., a new geometrid moth from Yunnan, China (Lepidoptera: Geometridae, Sterrhinae) - Sihvonen, Pasi (Zootaxa, 2005)
A new geometrid moth, Scopula anfractata Sihvonen sp. n., is described and illustrated from the northern part of Yunnan province, China. The facies of S. anfractata are distinct from its congeneres, with concave transverse median and posterior lines and an acute apex of the forewing, resembling some species of the ennomine genus Loxaspilates Warren. Adults and genitalia of both sexes of S. anfractata are compared with those of S. dubernardi (Oberthür, 1923), which is considered the most closely related species. The systematic position of the two species within Scopula Schrank is uncertain, but structures of the genitalia suggest affinities with the S. umbelaria species group. Scopula anfractata is known only from the type locality of Dayan (Lijiang), China; its biology and immature stages are unknown.